Ideational Basis of Civil Society Supporting the Sustainable Development Agenda - Kusumaningrum, Demeiati Nur; Kurniawati, Dyah Estu (Cities and Urban Development Journal, 2024)
Background: In discussing consumption and the environment as part of social change, Malang City and Regency become a study of the relationship between the state and civil society in efforts to overcome the challenges of climate change, one of which is the waste problem. Unfortunately, less attention to analyze how and why civil society supports the global development agenda. Aims: This article attempts to discuss the intersubjective factors that encourage the role of civil society in supporting the achievement of sustainable urban development targets. Methods: The research applies qualitative methods with content analysis referring to primary data sourced from interviews, observations, social media content and government publication documents accessed online. Secondary data was obtained from literature studies and analysis of news articles. Results: Through a constructivist perspective, the 'zero waste living' community is believed to act as a creative class and norm empowerment to support the realization of a sustainable city. The process of institutionalization and norm diffusion occurs in the interaction and communication of community networks at all levels of activity. Conclusion: There is a process of internalization of the norm of 'your trash is your responsibility' and the principle of 'prevent-sort-process' in intensive communication and interaction networks in interconnected areas, both in environmental activist community forums, student guardian/student guardian friendship forums, and citizen/ Family Empowerment and Welfare (PKK) forums.